Postmarketing surveillance of the oxidative stability for cooking oils, frying oils, and vanaspati supplied in the retail market - Tavakoli, Hamid Reza (Food Sci Nutr, 2019)
In this study, postmarketing surveillance (PMS) was conducted in terms of the parameters which are reliable indicators of the oxidative stability of cooking oils, frying oils, and vanaspati samples. The analyzed parameters were fatty acid composition, peroxide value (PV), free fatty acids (FFA), p‐anisidine value (p‐AV), induction period at 110°C (IP(110)) determined by Rancimat test, and TOTOX value. For this purpose, different samples from four highly popular brands of mentioned products were randomly collected from Iran's market during 2016–2018. All monitored products had trans fatty acid <1.0%. In the case of FFA and IP(110), the ranges of 0.03–0.08 (%) and 9.3–17.2 hr were obtained, respectively, being mostly in conformity with the National Standard of Iran (FFA < 0.1% and IP(110)  > 15 hr). The ranges of PV of cooking oils, frying oils, and vanaspati samples were 1.2–2.7, 0.93–2, and 0.84–1.6 meq/kg, respectively. Our results revealed that p‐AV of frying oils and cooking oils was mostly outside of legal limits of Iran (p‐AV > 6) with the ranges of 4.2–12.5 and 4.3–12.3, respectively. In terms of TOTOX value, monitored products had a range from 5.2 to 13.0 (mostly <10) being nearly acceptable.